Analysis of the Genomic Features and Evolutionary History of Pithovirus-Like Isolates Reveals Two Major Divergent Groups of Viruses - Queiroz, Victória F. (2023)
New representatives of the phylum Nucleocytoviricota have been rapidly described in the last decade. Despite this, not all viruses of this phylum are allocated to recognized taxonomic families, as is the case for orpheovirus, pithovirus, and cedratvirus, which form the proposed family Pithoviridae. In this study, we performed comprehensive comparative genomic analyses of 8 pithovirus-like isolates, aiming to understand their common traits and evolutionary history. Structural and functional genome annotation was performed de novo for all the viruses, which served as a reference for pangenome construction. The synteny analysis showed substantial differences in genome organization between these viruses, with very few and short syntenic blocks shared between orpheovirus and its relatives. It was possible to observe an open pangenome with a significant increase in the slope when orpheovirus was added, alongside a decrease in the core genome. Network analysis placed orpheovirus as a distant and major hub with a large fraction of unique clusters of orthologs, indicating a distant relationship between this virus and its relatives, with only a few shared genes. Additionally, phylogenetic analyses of strict core genes shared with other viruses of the phylum reinforced the divergence of orpheovirus from pithoviruses and cedratviruses. Altogether, our results indicate that although pithovirus-like isolates share common features, this group of ovoid-shaped giant viruses presents substantial differences in gene contents, genomic architectures, and the phylogenetic history of several core genes. Our data indicate that orpheovirus is an evolutionarily divergent viral entity, suggesting its allocation to a different viral family, Orpheoviridae.